Design and optimization of ultra-wideband antipodal vivaldi antenna for radar and microwave imaging application - Shaikh, Faraz Ahmed; Khan, Sheroz; Zaharudin, Zarimin; Alam, A. H. M. Zahirul; Yaacob, Mashkuri; Shahid, Zeeshan; Abdul Rahman, Farah Diyana; Badron, Khairayu (University of Sindh, 2018)
The functional characteristics and parametric study of Ultra-Wideband Antipodal Vivaldi Antenna along with end-fire radiation pattern via UWB frequency range for radar as well as microwave imaging application has presented in this paper. The comparative study of different kind of AVA according to their structure and dimension has been proposed. Although the basic design concept of conventional antipodal Vivaldi antenna has reported and initially designed for a broad impedance bandwidth performances. Furthermore, the modification of AVA by incorporates the corrugations edges on both side of basic AVA structure. As a result, high gain has achieved with improved directivity and observed a flat gain especially at low frequency. The modified design structure almost covered entire UWB bandwidth. The propose antenna structure and optimization method is conceded out by simulation software named CST. The validations of antenna performance parameters like return loss, input impedance and directivity through simulation software. Prototypes of both like conventional and proposed modified antennas have fabricated and verified intended for its return loss as well as directional pattern.